As tiras nos livros didáticos de língua portuguesa: uma proposta de leitura - Segate, Aline (2011)
The main objective of teaching Portuguese language is the students development of discursive competence, that is, developing in the students the ability to choose the appropriate genre in different communicative situations. Thus, Dolz and Schneuwly (2004) state the discursive genre must be principle which supports the work at schools, because these discursive entities collaborate for developing students language and also are dealt as object and resource tools by teachers in the classroom. PCNs (National Curriculum Parameters) propose the use of discursive genre as a teaching object for practicing reading/ writing as well as the genres may be considered great allied in the process of teaching and learning Portuguese. Therefore, from these points of view, this current research aims to analyze the teaching of reading by working with comic strips as proposal offered by several Portuguese language textbook collections (LDLP) by public state High schools in Uberlândia. The comic strip genre has been chosen because we believe that its transposition to the process of Portuguese teaching may lead to an interdisciplinary work which may be able to get students engaged in a critical formation towards to citizenship. We also believe the discursive genre s multimodal aspects may contribute for the textual comprehension, given the fact that in a communication situation the non-verbal aspects are as relevant as speech and writing. The research corpus consists of 16 comic strips from the selected LDPL. The research theory refers to Dionísio (2005), Kress e Van Leuwen (1996), Mendonça (2005), Ramos (2009), Vergueiro (2009), among other scholars who approach the theme. We have noticed that although the comic strips frequently appear in LPLP, the textbooks have not considered the genre peculiarities by mainly ignoring the comic strip non-verbal aspects which is the enriched discursive-argumentative aspect of the genre.